The haunted gallery : painting, photography, film c.1900 - Nead, Lynda (New Haven : Yale University Press, 2007)
- Velocities of the image c. 1900 ##- Haunted gallery ##- Animating the everyday ##- Paintings, films and fast cars ##- Strip : moving bodies in the 1890s ##- Lumen and the celestial archive of images.
Includes bibliographical references (p. [269]-283) and index.
boek